Istanbul in Domestic Migration Films (1965-1980) in Turkish Cinema: Stone and Soil Made of “Sorrow and Gloom” - Şeyma Balcı (İletişim Kuram ve Araştırma Dergisi)
The population of Istanbul, as the “city of immigrants”, has been continuously shaped with migration. Migration to the city was not much intense during the period from proclamation of the Republic to 1950. However, a wave of mass migration to Istanbul started after 1950. Cinema is another field where this transformation is made visible. In this context, with the purpose of finding out the way Istanbul was represented in domestic migration films shot in Turkish cinema between 1965-1980, the historical and sociological data of the domestic migration process were used along with the tropes in the study. The migrants’ reason of migrating to Istanbul, how they come, where and how they live, and what waits for them in the end were examined through the films named Bitmeyen Yol (Duygu Sağıroğlu, 1965), Ben Öldükçe Yaşarım (Duygu Sağıroğlu, 1965), Altın Şehir (Orhan Elmas, 1965), Öksüz (Bilge Olgaç, 1968), Fatma Bacı (Halit Refiğ, 1972), Sarı Öküz Parası (Nişan Hançeryan, 1972), Gelin (Ömer Lütfü Akad, 1973), Düğün (Ömer Lütfü Akad, 1974), Kızım Ayşe (Yücel Çakmaklı, 1974), Aç Gözünü Mehmet (Süreya Duru, 1974), Taşı Toprağı Altın Şehir (Orhan Aksoy, 1978), Yusuf ile Kenan (Ömer Kavur, 1979), and Baba Kartal (Cüneyt Arkın, 1979). In domestic migration films, Istanbul turns out to be a city of death, loss and struggle for life. The domestic migration characters either die or kill in Istanbul. The city/Istanbul is identified with a woman who does not open her doors to newcomers/ immigrants at once. Istanbul is far from being a city that leaves space for happy endings.